SOSIALISASI PELATIHAN MICROSOFT EXCEL BERBASIS VISUAL (DASHBOARD) UNTUK MENINGKATAN KOMPETENSI SISWA SMK NURUL HUDA BAROS - Arianto, Ichwan Putra; Jasmine, Veronika; Riska, Riska; Salsabila, Maulani Adinda; Alfiansyah, Pramudya (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
Community service is one of the contributions of universities in supporting human resource development, particularly in enhancing students' competencies. One of the barriers faced by students is their lack of visual skills in operating Microsoft Excel. This community service activity carries the theme "Socialization of Visual-Based Microsoft Excel Training (Dashboard) to Improve the Competencies of SMK Nurul Huda Baros Students." The main purpose of this activity is to provide students with an understanding of how to operate Microsoft Excel based on visual (dashboard). The implementation method is participatory, involving the delivery of material, interactive discussions, and simulations. The training includes an introduction to the basics of Microsoft Excel, function recognition, data table processing, and creating visual dashboards. The results show an increase in students' competence in using visual-based Microsoft Excel (dashboard). This activity is expected creating a generation people are outstanding, highly competitive, and morally upright.